Percepción y práctica de la responsabilidad social empresarial: el caso de las pyme de Salinas, Santa Elena (Estudios) - Suárez Rodríguez, Otto (2018)
This work seeks to determine the degree of knowledge and practice of corporate social responsibility (CSR) in SMEs in Salinas, Santa Elena. This tourist destination in the new province of Santa Elena in Ecuador has a small but dynamic local business sector in order to contribute to the development of its community. Through surveys applied to SMEs, CSR indicators were qualitatively assessed. The results indicate that CSR is more practiced by the entrepreneur’s values than by a conscious and systematic effort, which limits its impact on the development of the community.